Doppler shift velocimetry using two point probe nested-microring resonators - Jomtarak, Rangsan; Yupapin, Preecha P.; Ali, Jalil (My University, 2015)
In this paper, a micro Doppler shift velocimeter using two nested-microring resonators incorporating two gratings is designed and simulated. Two wavelength light pulse can be generated by a single input wavelength source after travelling through the two defect grating. Whispering gallery mode of light pulses are localized within the nested-microring resonators, which can be used to form the two point probe Doppler shift velocimeter. The shifted frequency (velocity) can be obtained by the difference of optical path length between two point probes, where the relative velocity of Doppler frequency shift velocimeter can be obtained. The light absorption behaviors can also be investigated by the different light output spectrum. The obtained simulation results shows that the relative velocities of the reflection and transmission light intensities are ranged from 104 m/s to 105 m/s, which can be useful for Doppler frequency shift velocimeter and sensors, where the micro-optical device and multi-functions are the advantages.
Keywords: Doppler shift velocimetry; microring resonators; Optical sensors; shift frequency